The prevalence of mandated and voluntary health information on alcohol products in Australia - Simone Pettigrew; Asad Yusoff; Bella Sträuli; Leon Booth; Paula O’Brien; Jacquie Bowden; Aimee Brownbill; Julia Stafford; Michelle I Jongenelis; Tazman Davies; Tanya Chikritzhs; Tim Stockwell; et al. (Australian and New Zealand Journal of Public Health)
Objective: Regulations to restrict alcohol promotion and requirements for mandatory display of information about health risks associated with alcohol use have been minimal and hard-won in Australia. This study (i) outlines an approach to monitoring alcohol industry use of health messages on alcohol products and (ii) reports prevalence and nature of government-mandated health-related information and voluntary health messages on alcohol products. Methods: Images of 5,923 alcohol products sold in four large alcohol stores in Sydney were captured. Data were collected in-store and via web-scraping. Label content was extracted from the images. Results: There was high compliance (97%-99%) with government-mandated requirements other than the pregnancy warning label (63%). Presence of voluntary health-related messages was common (65%), but typically present in the form of DrinkWise (an industry-led social aspects/public relations organisation) statements that are unlikely to be effective. Conclusions: This study provides a unique and systematic approach to examining alcohol industry compliance with government-mandated on-product information requirements and voluntary inclusion of other health-related messages. Implications for Public Health: The results demonstrate the need for ongoing monitoring to enforce alcohol industry compliance with Australia’s existing and future labelling regulations and to assess the industry’s voluntary use of other forms of health messaging.